High Performance Work System and Export Performance - Aqdas, Ramaisa; Abdullah, Nik Ab Halim Nik (Pakistan Journal of Humanities and Social Sciences, 2019)
This paper aims to propose a conceptual framework about the relationship between high performance work system practices and export performance. HPWS is expected to play a crucial role in organizational success. Thus, this paper proposed a framework for studying the relationship among four dimensions of HPWS such as recruitment and selection, performance management, compensation and rewards and training and development and export performance in Pakistan’s textile sector. Moreover, entrepreneurial orientation acts as the mediating factor among these variables. This framework is developed based on extensive literature and this study is expected to contribute towards knowledge by delivering insights and pointing out ways to increase country’s export performance. Specifically, this research will benefit Pakistan’s textile sector in formulating strategies to increase manufacturer’s export performance.